Design expert application for optimization of ag/agbr/tio2 visible light photocatalyst preparation - Affam, A.C. (Springer Science and Business Media Deutschland GmbH, 2021)
Titanium dioxide (TiO2) was activated under visible light after modification by doping with silver/silver bromide (Ag/AgBr) through simple impregnation-precipitation-photoreduction process. The use of central composite design tool of design expert in order to optimize the preparation parameters namely silver dopant, precipitation time and photoreduction time for the degradation of pesticide chloropyrifos was feasible. From the analysis of variance (ANOVA), the most influential factors affecting the experimental process and interaction was identified. The chemical oxygen demand (COD) removal increased with increasing the amount of Ag dopant and photoreduction time while precipitation time was not a significant factor. Optimized condition for preparation of the Ag/AgBr/TiO2 was mass ratio of Ag to TiO2: 1:1, precipitation time: 60 min, and photoreduction time: 90 min. Experimental COD removal efficiency was 77 while the predicted value was 77.4. The percentage error was 0.51. The close agreement between both predicted and actual COD removal shows good model. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.